Peran Guru Terhadap Motivasi Belajar Anak Berkebutuhan Khusus - Shafiana Azra; Sri Nurhayati Selian (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study discusses in depth the role of teachers in increasing the learning motivation of children with special needs who face various limitations, both physically, intellectually, and emotionally. Low learning motivation in these children is a major problem that can affect the learning process and academic results achieved. The main objective of this study is to determine the extent to which the role of teachers can influence, guide, and arouse children's enthusiasm for learning through an appropriate, humanistic, and individual-oriented approach. This study uses a descriptive qualitative method with data collection techniques in the form of direct observation, in-depth interviews with teachers, and documentation of various learning activities carried out. The subjects in this study were teachers who teach children with special needs at the Bukesra Foundation, an educational institution that specifically handles children with special needs. The results of the study show that teachers not only act as educators, but also as guides, facilitators, and motivators who are able to adjust teaching strategies according to the characteristics and needs of each child. These strategies include an individual approach, educational play methods, giving awards as a form of positive reinforcement, and creating a safe, fun, and empathetic learning atmosphere. This study concluded that active teacher involvement, combined with an empathetic and personal approach, had a significant impact on increasing the overall motivation and learning participation of children with special needs.